Web-Based Information System for Boarding House Information - Kurnia, Zefanya Yulius; Wijaya, Marvin Chandra (International Journal of Scientific Research and Management (IJSRM), 2024)
Web-Based Information System for Boarding House Information is a platform designed to facilitate efficient search and management of boarding houses. This research produces a system that allows boarding house owners to present complete information regarding facilities, prices and availability of boarding rooms through a user-friendly web interface. Prospective renters can quickly find boarding houses that suit their preferences, reducing time and effort in the housing search process. This system not only provides static information about boarding houses, but also provides real-time updates regarding room availability. With the implementation of this Web-Based Information System, it is hoped that it can increase the efficiency of boarding house management, increase the accessibility of information, and provide a better experience for boarding house seekers. This system is a leading solution in supporting the development of the housing industry, providing an easy-to-use platform to meet the needs of tenants and boarding house owners in this computerized period